A third human retinoic acid receptor, hRAR-gamma. - Krust, A (1989)
Retinoic acid receptors (RARs) are retinoic acid (RA)-inducible enhancer factors belonging to the superfamily of steroid/thyroid nuclear receptors. We have previously characterized two human RAR (hRAR-alpha and hRAR-beta) cDNAs and have recently cloned their murine cognates (mRAR-alpha and mRAR-beta) together with a third RAR (mRAR-gamma) whose RNA was detected predominantly in skin, a well-known target for RA. mRAR-gamma cDNA was used here to clone its human counterpart (hRAR-gamma) from a T47D breast cancer cell cDNA library. Using a transient transfection assay in HeLa cells and a reporter gene harboring a synthetic RA responsive element, we demonstrate that hRAR-gamma cDNA indeed encodes a RA-inducible transcriptional trans-activator. Interestingly, comparisons of the amino acid sequences of all six human and mouse RARs indicate that the interspecies conservation of a given member of the RAR subfamily (either alpha, beta, or gamma) is much higher than the conservation of all three receptors within a given species. These observations indicate that RAR-alpha, -beta, and -gamma may perform specific functions. We show also that hRAR-gamma RNA is the predominant RAR RNA species in human skin, which suggests that hRAR-gamma mediates some of the retinoid effects in this tissue.